First INTEGRAL and Swift observations of a giant outburst of A0535+26 - Caballero, I.; Müller, S.; Bordas, P.; Ferrigno, C.; Kühnel, M.; Pottschmidt, Katja; Kretschmar, P.; Wilms, J.; Kreykenbohm, I.; Klochkov, D.; Santangelo, A.; Staubert, R.; et al. (AIP, 2012)
The Be/X-ray binary A0535+26 has shown three giant outbursts since 2005, after a long period of quiescence. The giant outbursts in 2005 (~5.2 Crab, 15-50 keV range) and 2009 (~5.6 Crab) could not be observed by most X-ray observatories due to Sun observing constraints. Finally, a giant outburst in February 2011, that reached a flux of ~3.8 Crab, was monitored with INTEGRAL and Swift TOO observations. We present first results of these observations, with a special focus on the cyclotron lines present in the X-ray spectrum of the source.
SUZAKU 2011: Exploring the X-ray Universe: Suzaku and Beyond 20–22 July 2011 Palo Alto, California, USA